Miguel Must Fight! - Ofelia, Jamie; Palacios, Sara (New York : Little, Brown and Company, 2024)
When El Dragn̤ attacks, artistic Miguel must save his family and prove his colored pencils are mightier than their swords.
Ages 4-8.
In English with some Spanish words.
Keywords: Dragons -- Juvenile fiction; Families -- Juvenile fiction; Swords -- Juvenile fiction; Swordplay -- Juvenile fiction; Colored pencil drawing -- Juvenile fiction; Pencil drawing -- Juvenile fiction; Drawing -- Juvenile fiction; Individual differences -- Juvenile fiction; Dragons -- Fiction; Families -- Fiction; Swords -- Fiction; Swordplay -- Fiction; Colored pencil drawing -- Fiction; Pencil drawing -- Fiction; Drawing -- Fiction; Individual differences -- Fiction; Picture books